APPLICATION OF MAKE A MATCH METHOD TO IMPROVE ARABIC VOCABULARY UNDERSTANDING - Ellyda Retpitasari; Yasin Nur Falah (STKIP NU Kabupaten Tegal, 2021)
Starting from the problem of the weakness of students in mastering and understanding the material taught by the teacher, especially Arabic. Students find Arabic very boring and scary because they are lazy and reluctant to learn Arabic. So this study aims to describe the application of the Make A Match model in Arabic subjects with the Address of class IV students at MI Sabilul Muttaqin 02 Gandusari Blitar. This study uses two cycles of classroom action research. Each cycle consists of four stages, namely planning (planning), implementation (acting), observation (observation), and reflection (reflection), the target of this research is fourth-grade students in the Arabic language subject matter of Address. The data collection techniques used tests, interviews, observations, field notes, and documentation. The results of the study used by applying the Make A Match model showed an increase in student learning outcomes starting from the pre-test, post-test cycle I, to post-test cycle II. This can be seen from the average score of 59 students (pre-test), which increased to 69 (post test cycle I), and increased again to 83.9 (post test cycle II). Thus, to prove that the application of the Make A Match model improves Arabic learning outcomes for fourth grade students of MI Sabilul Muttaqin 02 Gandusari Blitar.